Factors Influencing the Performance of Accounting Information Systems with Education and Training as Moderating Variables - I Made Yoga Mahardika Raharja; Gede Juliarsa (E-Jurnal Akuntansi, 2025)
The study aimed to understand the factors influencing the performance of accounting information systems (AIS) at the Bali Regional Development Bank Headquarters in 2024, using education and training as a moderator. The research utilized the SPSS program with the Moderated Regression Analysis test tool. A total of 98 respondents were selected using the purposive sampling method. The results indicate that while the size of the organization and its interaction with education and training do not affect AIS performance, other factors and their interactions with education and training programs do significantly influence AIS performance.